Tandem application of ligand-based virtual screening and G4-OAS assay to identify novel G-quadruplex-targeting chemotypes - Musumeci, Domenica; Amato, Jussara; Zizza, Pasquale; Platella, Chiara; Cosconati, Sandro; Cingolani, Chiara; Biroccio, Annamaria; Novellino, Ettore; Randazzo, Antonio; Giancola, Concetta; Pagano, Bruno; Montesarchio, Daniela (Biochimica et biophysica acta. General subjects, 2017)
G-quadruplex (G4) structures are key elements in the regulation of cancer cell proliferation and their targeting is deemed to be a promising strategy in anticancer therapy. A tandem application of ligand-based virtual screening (VS) calculations together with the experimental G-quadruplex on Oligo Affinity Support (G4-OAS) assay was employed to discover novel G4-targeting compounds. The interaction of the selected compounds with the investigated G4 in solution was analysed through a series of biophysical techniques and their biological activity investigated by immunofluorescence and MTT assays. A focused library of 60 small molecules, designed as putative G4 groove binders, was identified through the VS. The G4-OAS experimental screening led to the selection of 7 ligands effectively interacting with the G4-forming human telomeric DNA. Evaluation of the biological activity of the selected compounds showed that 3 ligands of this sub-library induced a marked telomere-localized DNA damage response in human tumour cells. The combined application of virtual and experimental screening tools proved to be a successful strategy to identify new bioactive chemotypes able to target the telomeric G4 DNA. These compounds may represent useful leads for the development of more potent and selective G4 ligands. Expanding the repertoire of the available G4-targeting chemotypes with improved physico-chemical features, in particular aiming at the discovery of novel, selective G4 telomeric ligands, can help in developing effective anti-cancer drugs with fewer side effects. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio. [Display omitted] •60 putative G-quadruplex binders were identified by ligand-based virtual screening.•G4-OAS assay led to the selection of 7 effective ligands of telomeric G-quadruplex.•3 compounds were able to induce a significant DNA damage response at telomeres.•DNA damage caused by treatment with compound 10B correlates with cytotoxic activity.